2019
DOI: 10.12998/wjcc.v7.i2.171
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of exosomes as potential biomarkers in cancer

Abstract: BACKGROUNDExosomes are microvesicles, measuring 30-100 nm in diameter. They are widely distributed in body fluids, including blood, bile, urine and saliva. Cancer-derived exosomes carry a wide variety of DNA, RNA, proteins and lipids, and may serve as novel biomarkers in cancer.AIMTo summarize the performance of exosomal biomarkers in cancer diagnosis and prognosis.METHODSRelevant publications in the literature were identified by search of the “PubMed” database up to September 11, 2018. The quality of the incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
100
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(101 citation statements)
references
References 95 publications
0
100
1
Order By: Relevance
“…Cancer cells abundantly produce exosomes, and plasma of patients with cancer is enriched in tumor cell derived-exosomes. As the molecular content (such as miRNAs and proteins) of these exosomes recapitulate contents of the parent cell, they appear as possible non-invasive biomarkers of tumor progression and tumor angiogenesis [149] (Fig. 5a).…”
Section: Perspectivementioning
confidence: 99%
“…Cancer cells abundantly produce exosomes, and plasma of patients with cancer is enriched in tumor cell derived-exosomes. As the molecular content (such as miRNAs and proteins) of these exosomes recapitulate contents of the parent cell, they appear as possible non-invasive biomarkers of tumor progression and tumor angiogenesis [149] (Fig. 5a).…”
Section: Perspectivementioning
confidence: 99%
“…One of the most common alternative approaches under consideration for use of EVs as biomarkers is that of the dosage of the RNA species, particularly of miRs, determined by qRT-PCR followed by protein assessment, using either ELISA or mass spectrometry [ 199 ]. However, a major problem that may arise, particularly in assessing RNAs content in EVs, is that of sensitivity of RNA species to particular transport and storage conditions.…”
Section: Evs Used As Diagnostic Markersmentioning
confidence: 99%
“…The significance of exosomes in the cell to cell communication and transportation of unique genetic materials could be considered as biomarkers in the diagnosis and therapy of various diseases. Cancer studies showed that exosomes can be considered as potential biomarkers in diagnosis and prognosis of cancer (Wong and Chen, 2019). Besides, it was also revealed that DNM3, p65, and p53 followed a dysregulated-patterns in the brain and blood exosomes in both original and recurrent stages of glioblastoma multiforme.…”
Section: Introductionmentioning
confidence: 99%